2005
DOI: 10.1021/jp051682l
|View full text |Cite
|
Sign up to set email alerts
|

DFT Characterization of Adsorbed NHx Species on Pt(100) and Pt(111) Surfaces

Abstract: Periodic density functional theory (DFT) calculations using plane waves have been performed to systematically investigate the adsorption and relative stability of ammonia and its dehydrogenated species on Pt(111) and Pt(100) surfaces. Different adsorption geometries and positions have been studied, and in each case, the equilibrium configuration has been determined by relaxation of the system. The vibrational spectra of the various ammonia fragments have been computed, and band assignments have been compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
126
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 49 publications
19
126
2
Order By: Relevance
“…Density functional theory (DFT) calculations also support that the adsorption of the NH 2 fragment is more favorable on Pt (100) than on Pt (111) [78]. Besides, DFT calculations indicate a much lower adsorption energy of the atomic nitrogen on Pt (100) than that on Pt (111) and Pt (110), slowing down the deactivation process of Pt (100) [78]. This could explain the high activity of the Pt (100) surface.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Density functional theory (DFT) calculations also support that the adsorption of the NH 2 fragment is more favorable on Pt (100) than on Pt (111) [78]. Besides, DFT calculations indicate a much lower adsorption energy of the atomic nitrogen on Pt (100) than that on Pt (111) and Pt (110), slowing down the deactivation process of Pt (100) [78]. This could explain the high activity of the Pt (100) surface.…”
Section: Resultsmentioning
confidence: 91%
“…However, Pt (111) surface gives a deeper dehydrogenation of NH 3,ads to strongly adsorbed NH and N fragments, which fails to form N 2 at an appreciable rate [74]. Density functional theory (DFT) calculations also support that the adsorption of the NH 2 fragment is more favorable on Pt (100) than on Pt (111) [78]. Besides, DFT calculations indicate a much lower adsorption energy of the atomic nitrogen on Pt (100) than that on Pt (111) and Pt (110), slowing down the deactivation process of Pt (100) [78].…”
Section: Resultsmentioning
confidence: 96%
“…Despite outstanding theoretical studies in the topic of ammonia synthesis over a number of surfaces, 26-28 only few theoretical works have systematically examined the fragmentation of adsorbed NH x species on Pt(111), [29][30][31] Pd(111), 32 and Rh(111). 33 In fact, ammonia dehydrogenation studies over (100) surfaces are to the best of our knowledge not reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work 30 assessed the adsorption and relative stability of ammonia and the resulting dehydrogenated NH x species (x ) 0, 1, 2) on Pt(111) and Pt(100) surfaces using periodic slab DFT calculations. NH 3 and NH 2 were found to be more stable on Pt(100) than on Pt(111), while NH and N exhibited similar stabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation